The thin red line between species – genomic differentiation of Gymnosoma Meigen, a taxonomically challenging genus of parasitoid flies (Diptera: Tachinidae). (25th August 2020) - Lee, Kyung Min; Zeegers, Theo; Mutanen, Marko; Pohjoismäki, Jaakko
Abstract: In traditional taxonomy, species are differentiated using morphological arguments, which can be subjective and cause confusion particularly when the initial species descriptions have been inadequate. The development of DNA‐based methods has provided more objective tools to recognize and quantify species differences, as well as enabled the detection of cryptic that is morphologically indistinguishable, species. Conversely, we show here that large‐scale, genome‐wide analysis of 11 427 loci and 65 825 SNPs is mostly unable to differentiate between many of the currently valid Palearctic species of bug‐killing parasitoid flies in the genus Gymnosoma Meigen (Diptera: Tachinidae), despite the proposed morphological differences. We conclude that alongside a few well‐defined taxa with discrete morphological features and unique DNA barcodes, Palearctic Gymnosoma is likely to contain a single, highly variable and geographically widespread species. Abstract : Genomic methods are unable to distinguish between many of the currently valid species of Palearctic Gymnosoma. The suggested Gymnosoma rotundatum species group contains poorly differentiated clades with evidence of gene flow between them. Extreme morphological variation among G. rotundatum group, including male terminalia, mimics species differences and explains the difficulties in species assignments.